The Maghreb-Europe paradigm : migration, gender and cultural dialogue - Ennaji, Moha (Cambridge Scholars Publishing, 2019)
This book discusses the current socio-cultural situation of North African migrants in Europe, and analyzes migration, gender, and identity in their multiple dimensions, consequences and expressions, which range from sociological approaches to culture and literature. The chapters debate the topic of migration and culture from various angles, making this volume a forum where notions of dispossession, cultural identity, and otherness are debated. It comprises contributions that range in subject matter from sociological and anthropological studies of Maghrebi diaspora and migrants in Europe to ref.